EFEKTIVITAS PENERAPAN MEDIA GAME BAAMBOOZLE UNTUK MENINGKATKAN MINAT DAN MOTIVASI SISWA PADA PEMBELAJARAN NILAI TEMPAT BILANGAN CACAH KELAS IV SDN 46 BANDA ACEH - Maharani; Rita Novita; Tria Marvida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Matematics learning in elementary school is often seen as difficult and not interesting, which makes students lose their interest and enthusiasm for studying. The same situation also happens in class IV at SDN 46 Banda Aceh, where students appear to be less active, not enthusiastic, and not interested during math lessons. One way to deal with this problem is by using interactive and engaging learning tools, such as the Baamboozle game. Media Baamboozle is a learning tool that uses games, helping students to be more engaged and interested in learning in a fun way. This study uses a quantitative method with a pre-experimental design in the form of a single-group model, which includes pre-testing and post-testing. The population and sample in this research are all the fourth-grade students at SDN 46 Banda Aceh, totaling 28 students. Data collection techniques involved using survey sheets about students' interests and learning motivation that were given before and after the use of the media, along with direct observations and documentation records. The data analysis was done using descriptive statistical methods, normality testing with the Shapiro-Wilk method, paired comparison testing with the t-test, and measurement of ability improvement using the N-Gain method.